Gene expression responses to Rice tungro spherical virus in susceptible and resistant near-isogenic rice plants - Satoh, Kouji; Kondoh, Hiroaki; De Leon, Teresa B.; Macalalad, Reena Jesusa A.; Cabunagan, Rogelio C.; Cabauatan, Pepito Q.; Mauleon, Ramil; Kikuchi, Shoshi; Choi, Il-Ryong (Virus research, 2013)
► Transcriptome in rice plants asymptomatically infected with RTSV was analyzed. ► Gene expression specific to RTSV-resistant and -susceptible plants was revealed. ► Many defense and development-related genes were regulated in asymptomatic plants. Rice cultivar Taichung Native 1 (TN1) is susceptible to Rice tungro spherical virus (RTSV). TW16 is a backcross line developed between TN1 and RTSV-resistant cultivar Utri Merah. RTSV accumulation in TW16 was significantly lower than in TN1, although both TN1 and TW16 remained asymptomatic. We compared the gene expression profiles of TN1 and TW16 infected by RTSV to identify the gene expression patterns accompanying the accumulation and suppression of RTSV. About 11% and 12% of the genes in the entire genome were found differentially expressed by RTSV in TN1 and TW16, respectively. About 30% of the differentially expressed genes (DEGs) were detected commonly in both TN1 and TW16. DEGs related to development and stress response processes were significantly overrepresented in both TN1 and TW16. Evident differences in gene expression between TN1 and TW16 instigated by RTSV included (1) suppression of more genes for development-related transcription factors in TW16; (2) activation of more genes for development-related peptide hormone RALF in TN1; (3) TN1- and TW16-specific regulation of genes for jasmonate synthesis and pathway, and genes for stress-related transcription factors such as WRKY, SNAC, and AP2-EREBP; (4) activation of more genes for glutathione S-transferase in TW16; (5) activation of more heat shock protein genes in TN1; and (6) suppression of more genes for Golden2-like transcription factors involved in plastid development in TN1. The results suggest that a significant number of defense and development-related genes are still regulated in asymptomatic plants even with a very low level of RTSV, and that the TN1- and TW16-specific gene regulations might be associated with regulation of RTSV accumulation in the plants.